Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja pada Dinas Kependudukan dan Catatan Sipil Kota Gorontalo - Anwar, Sitti Meylani Karina; Ariawan; Rahmisyari (Melati Institute, 2024)
This study aims to analyze and explain the Influence of Leadership and Work Discipline on Employee Performance Through Job Satisfaction at the Population and Civil Registration Office of Gorontalo City. The type of research used is quantitative with a survey method. The unit of analysis used is the individual. The collection of basic data used using a survey, the number of samples in this study was 64 respondents. The analysis method used is SEM PLS. The results of the study show that (i). Leadership (X1) has a positive and significant effect on Job Satisfaction (Z) at the Population and Civil Registration Office of Gorontalo City, (ii). Work Discipline (X2) has a positive and significant effect on Job Satisfaction (Z) at the Population and Civil Registration Service of Gorontalo City, (iii). Leadership (X1) has a positive and significant effect on Employee Performance (Y) at the Population and Civil Registration Service of Gorontalo City, (iv). Work Discipline (X2) has a positive and insignificant effect on Employee Performance (Y) at the Population and Civil Registration Service of Gorontalo City, (v). Job Satisfaction (Z) has a positive and significant effect on Employee Performance (Y) at the Population and Civil Registration Service of Gorontalo City, (vi). Leadership (X1) has a positive and significant effect on Employee Performance (Y) with Job Satisfaction (Z) as an intervening variable at the Population and Civil Registration Service of Gorontalo City (vii). Work Discipline (X2) has a positive and significant effect on Employee Performance (Y) with Job Satisfaction (Z) as an intervening variable at the Population and Civil Registry Service of Gorontalo City